Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan dan Sikap Remaja Tentang Seks Bebas - Fitriani Fitriani; Nur Ekawati; Dewi Sartika MS; Nelly Nugrawati; Siti Alfah (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Indonesian teenagers seem to be more tolerant of premarital sexual lifestyles or promiscuous sex. Many factors influence this behavior, one of which is the attitude and knowledge about the free sex itself. This knowledge and attitude can be improved by providing counseling or health education. Purpose: Knowing the effect of health education on adolescents' knowledge and attitudes about promiscuous sex. Method: Pre-Experimental type of research with the research design is One Group pre-test post-test design. The sample of this study included 84 students at SMK Negeri 6 Makassar using Cluster Sampling as a sampling technique for the Research Instrument using a questionnaire. The data analysis used is bivariate analysis, Paired Sample T test. Results: Showed that there was an increase in the number of respondents who had good knowledge between before and after health education, namely an average change of 7,131 (± 3,229) by 98.8% with a p value of 0.000. And there was an increase in the number of respondents who had a good attitude between before and after health education, namely an average change of 3,917 (± 3,860) by 100% with a p value of 0.000. Conclusion: That there is an influence of health education on students' knowledge and attitudes (i) about promiscuous sex.